Landscape Design of Adaptive Mangrove Ecotourism Based on Ecology And Socio-Economy of The Community of Batu Ampar Anambas Village (Agrikan Jurnal Agribisnis Perikanan, 2024)
Ecotourism is tourism that prioritizes environmental ethics by preserving nature, providing economic benefits, and respecting local cultural wisdom. The purpose of the research to be carried out is to analyze the ecological condition of mangroves in the mangrove ecotourism area of Batu Ampar Village, Kute Siantan District, Anambas Islands Regency, Analyze the socio-economic conditions of the Management Community, Tourists and the Government of Batu Ampar Village, Kute Siantan District, Anambas Islands Regency, Formulate Adaptive Mangrove Ecotourism Landscape Design planning based on the ecological and socio-economic characteristics of the Batu Ampar Village Community, Kute Siantan District, Anambas Islands Regency. This research uses quantitative and qualitative approaches that refer to ecological and socio-economic aspects. the results of this study indicate that Batu Ampar village has a tree density that is included in the â€œvery suitableâ€ category for mangrove ecotourism, with tree densities ranging from 1,233 to 2,425 individuals/ha. The average mangrove thickness is 80.80 m in the area that is the tourist site. There are 14 species of biota present in the mangrove ecosystem, covering diverse groups such as crustaceans, fish, molluscs, birds, reptiles and mammals. The improvement strategy prioritizes visitor satisfaction and improving the economy of the management community by improving infrastructure facilities
Keywords: Ekowisata Mangrove; Adaptif; Pengembangan; Ekowisata